UMP In-Smartive Club members’ meaningful trip at UTY - Wan Nazrul Helmy, Wan Mohd Zain
A total of 23 Universiti Malaysia Pahang (UMP) undergraduates took time off to experience the way of life of peasants away in a village in Indonesia while their friends returned to their homes and families during the final semester break.